Optimasi waktu pemanasan awal dan waktu pasteurisasi PEF terhadap asam lemak bebas, vitamin C, dan pH pada pengolahan susu - Angky Wahyu Putranto; Anugerah Dany Priyanto; Widyasari Widyasari; Yushinta Aristina Sanjaya; Teti Estiasih (AGROINTEK, 2022)
RSM (Response Surface Methodology) is one method that is widely used for process optimization. The purpose of this study was to obtain the optimum combination of treatments in milk processing. The combination of treatments given was pre-heating time and pulsed electric field time with response levels of free fatty acids (%), vitamin C (mg/ml), and pH. The pre-heating temperature used was 70ºC and the voltage of pulsed electric field was 15 kV/cm. Software Design Expert 13 was used to optimize the milk processing. The optimum condition obtained was a combination of heating time treatment for 5 minutes and pulsed electric field time of 135.608 seconds. The combination of these treatments resulted in a response of free fatty acids levels of 0.002%, vitamin C of 0.217 mg/ml, and pH value of 7.087. The desirability results or results accuracy of the optimum solution show a value of 0.441. The PEF utilization as a low-temperature milk processing can improve milk quality. Optimization of the use initial temperature in combination with PEF is usefull for the effectiveness of milk processing